Rock support and reinforcement practice in mining : proceedings of the International Symposium on Ground Support : Kalgoorlie, Western Australia, 15-17 March 1999 /: proceedings of the International Symposium on Ground Support : Kalgoorlie, Western Australia, 15-17 March 1999. (2018) - Unknown
No abstract available